Mapping the human praxis network: an investigation of white matter disconnection in limb apraxia of gesture production. Issue 1 (13th January 2022) - Rosenzopf, Hannah; Wiesen, Daniel; Basilakos, Alexandra; Yourganov, Grigori; Bonilha, Leonardo; Rorden, Christopher; Fridriksson, Julius; Karnath, Hans-Otto; Sperber, Christoph
Abstract: Left hemispheric cerebral stroke can cause apraxia, a motor cognitive disorder characterized by deficits of higher-order motor skills such as the failure to accurately produce meaningful gestures. This disorder provides unique insights into the anatomical and cognitive architecture of the human praxis system. The present study aimed to map the structural brain network that is damaged in apraxia. We assessed the ability to perform meaningful gestures with the hand in 101 patients with chronic left hemisphere stroke. Structural white matter fibre damage was directly assessed by diffusion tensor imaging and fractional anisotropy mapping. We used multivariate topographical inference on tract-based fractional anisotropy topographies to identify white matter disconnection associated with apraxia. We found relevant pathological white matter alterations in a densely connected fronto-temporo-parietal network of short and long association fibres. Hence, the findings suggest that heterogeneous topographical results in previous lesion mapping studies might not only result from differences in study design, but also from the general methodological limitations of univariate topographical mapping in uncovering the structural praxis network. A striking role of middle and superior temporal lobe disconnection, including temporo-temporal short association fibres, was found, suggesting strong involvement of the temporal lobe in the praxis network. Further, the results stressed the importance of subcortical disconnections for the emergence of apractic symptoms. Our study provides a fine-grain view into the structural connectivity of the human praxis network and suggests a potential value of disconnection measures in the clinical prediction of behavioural post-stroke outcome. Abstract : Rosenzopf et al . mapped white matter disconnection underlying limb apraxia and found a white matter network including inferior frontal and parietal, middle and superior temporal and precentral and subcortical areas to be involved in deficits in the production of communicative gestures. Graphical Abstract: